ENGLISH ROMANTICISM AND ITS DEVELOPMENT - Bozorboyeva Farangiz; Khamitov Eldorbek Erkin o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
English Romanticism was a literary and artistic movement that emerged in the late 18th century, reaching its peak in the first half of the 19th century. This period was characterized by a shift in artistic and intellectual focus towards the individual, nature, and the imagination. Romanticism was a reaction against the Industrial Revolution, the Enlightenment, and the rationalism of the 18th century. During this time, poets, writers, and artists sought to explore e English Romanticism was a literary and artistic mov motions, imagination, and the beauty of nature. They emphasized the importance of individual expression and freedom, valuing intuition over reason. Some key themes in Romantic literature include a celebration of nature, a focus on the supernatural and the sublime, an exploration of the self and individiuality.